Coach decision-making and the relative age effect on talent selection in football - Hill, B. A.; Sotiriadou, P. (European Sport Management Quarterly, 2016)
Research Question(s): Talent selection is a stepping stone to sporting success at national and international levels. The research questions that guided this study were: (a) What is the decision-making (DM) process that coaches (as key selectors) use during talent selection? and (b) In what ways does awareness of the relative age effect (RAE) influence their DM? Research Methods: This study employed an action research approach in order to raise coach awareness of RAE on talent selection to examine the decisions surrounding selection of players. From a sample of 263 male football (soccer) players (age range 12-15) and 4 coaches, qualitative and quantitative data were collected on coach decisions for selection of players and frequencies of selected players in birth-months. Secondary data were also gathered from previous year`s selections. Results and Findings: Logistic regression showed that coaches` awareness of RAE did not eliminate nor reduce it. In-depth interviews revealed that coaches` DM was influenced by preconceptions and various pressures to select certain players. Pressures resonated within the volatile nature of their profession and career goals, the existence of competing decision-makers such as peers and parents, and the tension to select players for immediate success. Implications: The results lead to the consideration of various practical recommendations on coach organisation, coach education and alternative interventions in DM such as an alternative staged approach to talent selection that lends itself open for future research. Coach decision-making and the relative age effect on talent selection in football. Available from: https://www.researchgate.net/publication/301622202_Coach_decision-making_and_the_relative_age_effect_on_talent_selection_in_football